A primary plus secondary local PWHT method for mitigating weld residual stresses in pressure vessels. (August 2021) - Jin, Qiang; Jiang, Wenchun; Gu, Wenbin; Wang, Jinguang; Li, Gang; Pan, Xiaodong; Song, Ming; Zhang, Kai; Wu, Aibing; Tu, Shan-Tung
Abstract: Local post-weld heat treatment (PWHT) is often used for mitigating welding-induced residual stresses in pressure vessels and piping systems. As large and ultra-large pressure vessels are increasingly used in petrochemical and power generation industries, traditional local PWHT procedures stipulated in Codes and Standards become difficult to implement for some of the ultra-large vessels due to their very large diameter and overall length. In this paper, a new method referred to as primary-secondary heating based local PWHT technique (PS-PWHT) is proposed. Both finite element residual stress modeling and experimental residual stress measurements were performed for both validating the effectiveness of the proposed technique and elucidating the underling mechanisms. The results show that the PS-PWHT method can reduce welding-induced residual stresses in a significant manner, even leading to some level of compressive residual stresses at the vessel weld region. Graphical abstract: Image 1 Highlights: A new secondary tensile thermal stress is generated on the inner surface by local PWHT. The inner surface stress of cylinder does not drop but rises due to the waist deformation. The secondary heating can mitigate the waist deformation of the weld through anti-deformation. The method can suppress the risk of stress corrosion cracking from residual stress standpoint.